Mother-young bond in non-human mammals: Neonatal communication pathways and neurobiological basis - Mota-Rojas, Daniel; Bienboire-Frosini, Cécile; Marcet-Rius, Míriam; Domínguez-Oliva, Adriana; Mora-Medina, Patricia; Lezama-García, Karina; Orihuela, Agustín (Frontiers in Psychology, 2022)
Mother-young bonding is a process by which the young establish social preferences for their mother. It fosters reproductive success and the survival of offspring by providing food, heat, and maternal care. This process promotes the establishment of the mother-young bond through the interaction of olfactory, auditory, tactile, visual, and thermal stimuli. The neural integration of multimodal sensory stimuli and attachment are coordinated into motor responses. The sensory and neurobiological mechanisms involved in filial recognition in precocial and altricial mammals are summarized and analyzed in this review.